Study Effect of Clarithromycin drug on Cryptosporidium Parvum and Efficiency of ELISA Technique in Diagnosis Comparison with Some Traditional Methods in vitro - Hussein A. Kadhum1, Shaimaa A. Shlash2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This research aimed to study effect of Clarithromycin drug on Cryptosporidium Parvum and efficiency of ELISA technique in diagnosis comparison with some traditional methods in vitro. Samples collected from four different sources water were 400 liters:100 liters tap water provider by Al-Kufa District River,100 liters house tank water,100 liters from sea of Al-Najaf and 100 liters stagnant water during period from October 2018 to April 2019.Examined samples by three laboratory methods: Modified Ziehl-Neelson stain, Flotation by saturated sugar solution method and ELISA to detecting from Cryptosporidium oocysts in the water as used Clarithromycin drug effective against C.parvum in vitro. Capability test was implement impregnation isolated and determination cells of parasite counted when at 37°C/ 48h incubated. Differ concentrations from Clarithromycin were 4, 8, 16 and 32 mg/L respectively compared with control group.Results of the current study showed that oocysts were found in 182 from 400 liters 45.5% as showed that height oocysts in stagnant water then followed Sea of Al-Najaf were 55% and 45% respectively, height percentage of oocysts were in April and March were 69.09% and 66% while decrease percentage of infection in October was 25%. As showed study results presence significant differences in efficiency of ELISA technique was 83.33% at detection from oocysts compared with Flotation by saturated sugar solution and Modified Ziehl-Neelson stain methods were 66.66% and 61.11% respectively. Shown results this study that Clarithromycin with 16 and 32 mg/L lead to reduction in number oocysts was 17.3±3.5 and 15.4±3.9, sporozoites counts was 17.1±3.4 and 14.9±4.0 compared with control group was 20.5±2.8.As observed significance differences P.0.05 in the mean numbers the oocysts and sporozoites in three replicate plates after 48 h. These results proved that Clarithromycin have effectiveness in inhibition C.parvum in vitro.